2022
DOI: 10.1292/jvms.21-0609
|View full text |Cite
|
Sign up to set email alerts
|

<i>In vitro</i> efficacy of <i>Capparis spinosa</i> extraction against larvae viability of <i>Echinococcus granulosus</i> sensu stricto

Abstract: Cystic echinococcosis (CE) is a chronic zoonotic parasitic disease caused by infection with the larvae of the Echinococcus granulosus sensu lato (s.l.) cluster. Currently, new drugs are urgently required due to the poor therapeutic effect of the existing drugs albendazole and mebendazole. Capparis spinosa , a traditional medicinal plant, has potential therapeutic effects on various diseases based on extracts from its fruit and other parts. The results of this study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 33 publications
(36 reference statements)
0
2
0
1
Order By: Relevance
“…Screening active compounds from natural medicinal plants has gained importance in the field of parasitic infections. 20,27 The discovery of artemisinin and its use in malaria is seen as strong evidence of this approach. 28 Previous work demonstrated that HM exhibits anti-E. granulosus s.s. effects, but its toxicity is not negligible.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Screening active compounds from natural medicinal plants has gained importance in the field of parasitic infections. 20,27 The discovery of artemisinin and its use in malaria is seen as strong evidence of this approach. 28 Previous work demonstrated that HM exhibits anti-E. granulosus s.s. effects, but its toxicity is not negligible.…”
Section: Discussionmentioning
confidence: 99%
“…PSCs were collected for observation by scanning electron microscopy (SEM) (LEO1430VP, LEO company, Germany) after drug intervention, and the experiments were performed as previously described. 20 …”
Section: Methodsmentioning
confidence: 99%
“…Após 24 dias de intervenção com os extratos de C. spinosa, o tegumento dos protoescoleces apresentavam grande número de bolhas, o rostro foi destruído, os ganchos foram perdidos e as microtríquias foram eliminadas. Os extratos também diminuíram a viabilidade dos metacestodas, com perda ou destruição das células germinais da camada germinal(Yan et al, 2022). Ampelopsina diminuiu a viabilidade dos protoescoleces de E. granulosus, levando a morte de cerca de 60% deles após 7 dias de tratamento com as maiores concentrações.Por microscopia óptica, foram observadas distorção, vesiculação e vacuolização no escólex, e bolhas no tegumento dos protoescoleces tratados com ampelopsina.…”
unclassified